Open Source for Seeds and Genetic Sequence Data: Practical experience and future strategies - Louafi, Sélim; Westphal, Ida; Montenegro, Maywa; Manzella, Daniele; Otieno, Gloria; Steigerwald, Sophie; Kloppenburg, Jack (Perspective, 2018)
Version française de l'article Application of the open source concept to seeds has a promising future. It reverses the logic of the intellectual property system with a renewable stock of open source material kept outside the exclusive intellectual property realm. Legal defensibility may currently be uncertain, but as open source builds a critical mass of practitioners and supporters, wider social legitimacy could strengthen the legal power. Future extension to other subject matter and settings is discussed on the basis of lessons learnt from current open source seed implementation experience in the US, Europe and Africa.